Comparative Analysis of COVID‐19 Severity and Mortality Among Vaccinated and Unvaccinated Individuals During the Delta Variant Surge in a Tertiary Care Center: A Cohort Study - Fatemeh Hasani; Zahra Norouzi; Kimia Jazi; Gholamreza Roshandel; Alireza Norouzi (Health Science Reports)
ABSTRACT Background and Aims On March 11, 2020, the World Health Organization declared Coronavirus disease 2019 (COVID‐19) as a pandemic. The spread of the Delta variant of coronavirus started in June 2021 and accounted for the fifth peak of COVID‐19 in Iran in July 2021. According to reports from other countries, vaccination protects against severe diseases caused by COVID‐19, including the Delta variant. Studies have also shown that vaccination provides strong protection against SARS‐CoV‐2 infection, COVID‐19‐related hospitalization, and mortality. This retrospective cohort study was designed based on the medical care monitoring center database of Sayyad Shirazi Hospital. Methods COVID‐19 confirmed patients' data were extracted for this study from June 22, 2021, to September 22, 2021 including demographic characteristics, signs and symptoms, ICU admission, need for aggressive oxygen therapy, including intubation, mortality, and vaccination status. Results A total of 2962 patients were enrolled. Being vaccinated was associated with a 4.14‐fold increase in survival (adjusted OR = 4.14; 95% CI: 2.22–7.69; p < 0.01), and individuals in a younger age group demonstrated a 5.58‐fold higher likelihood of surviving (adjusted OR = 5.58; 95% CI: 4.25–8.14; p < 0.01). The risk of severe COVID‐19 was significantly lower in vaccinated individuals, showing a 3.12‐fold decrease in risk (adjusted OR = 3.12; 95% CI: 2.06–4.72; p < 0.01), and in younger age groups, the risk exhibited a 3.28‐fold decrease (adjusted OR = 3.28; 95% CI: 2.66–4.04; p < 0.01). Conclusion The present results suggest that receiving at least one dose of COVID‐19 vaccine had a significant relationship with decreased COVID‐19 severity and mortality in vaccinated patients compared to unvaccinated patients.